Occurrence and distribution of the heterotrophic straminipiles from Brazilian Atlantic Rainforest areas - Pires-Zottarelli, Carmen Lidia Amorim (2023)
We present herein the occurrence and distribution of the heterotrophic straminipiles collected from soil and water, submerged leaves and surface sediment from freshwater bodies at “Mosaico de Unidades de Conservação Juréia-Itatins”, a preserved conservation unit of the Brazilian Atlantic Rainforest. From 180 collected samples, we isolated 41 taxa belonging to Hyphochytriomycota and Oomycota using the multiple baiting technique, with several new taxa to the science, new occurrences to São Paulo State or Brazil, and all new citation to the studied area. These taxa were identified based on morphological and/or molecular data, with several genic regions made available in GenBank. The calculated community structure of these zoosporic organisms showed a diverse community, with few dominant taxa, without significant differences (P≤0.05) among the different types of samples.